Local recurrence of prostate cancer after radical prostatectomy is at risk to be missed in 68Ga-PSMA-11-PET of PET/CT and PET/MRI: comparison with mpMRI integrated in simultaneous PET/MRI - Freitag, Martin T.; Radtke, Jan Philipp; Afshar-Oromieh, Ali; Hadaschik, Boris; Wieczorek, Kathrin; Flechsig, Paul; Giesel, Frederik L.; Hohenfellner, Markus; Haberkorn, Uwe; Schlemmer, Heinz-Peter; Dimitrakopoulou-Strauss, Antonia (European journal of nuclear medicine and molecular imaging, 2017)
PurposeThe positron emission tomography (PET) tracer 68Ga-PSMA-11, targeting the prostate-specific membrane antigen (PSMA), is rapidly excreted into the urinary tract. This leads to significant radioactivity in the bladder, which may limit the PET-detection of local recurrence (LR) of prostate cancer (PC) after radical prostatectomy (RP), developing in close proximity to the bladder. Here, we analyze if there is additional value of multi-parametric magnetic resonance imaging (mpMRI) compared to the 68Ga-PSMA-11-PET-component of PET/CT or PET/MRI to detect LR.MethodsOne hundred and nineteen patients with biochemical recurrence after prior RP underwent both hybrid 68Ga-PSMA-11-PET/CTlow-dose (1 h p.i.) and -PET/MRI (2-3 h p.i.) including a mpMRI protocol of the prostatic bed. The comparison of both methods was restricted to the abdomen with focus on LR (McNemar). Bladder-LR distance and recurrence size were measured in axial T2w-TSE. A logistic regression was performed to determine the influence of these variables on detectability in 68Ga-PSMA-11-PET. Standardized-uptake-value (SUVmean) quantification of LR was performed.ResultsThere were 93/119 patients that had at least one pathologic finding. In addition, 18/119 Patients (15.1%) were diagnosed with a LR in mpMRI of PET/MRI but only nine were PET-positive in PET/CT and PET/MRI. This mismatch was statistically significant (p = 0.004). Detection of LR using the PET-component was significantly influenced by proximity to the bladder (p = 0.028). The PET-pattern of LR-uptake was classified into three types (1): separated from bladder; (2): fuses with bladder, and (3): obliterated by bladder). The size of LRs did not affect PET-detectability (p = 0.84), mean size was 1.7 ± 0.69 cm long axis, 1.2 ± 0.46 cm short-axis. SUVmean in nine men was 8.7 ± 3.7 (PET/CT) and 7.0 ± 4.2 (PET/MRI) but could not be quantified in the remaining nine cases (obliterated by bladder).ConclusionThe present study demonstrates additional value of hybrid 68Ga-PSMA-11-PET/MRI by gaining complementary diagnostic information compared to the 68Ga-PSMA-11-PET/CTlow-dose for patients with LR of PC.